Biodegradable polyester unimolecular systems as emerging materials for therapeutic applications. Issue 35 (28th August 2018) - Liu, Xuan; Fan, Xiaoshan; Jiang, Lu; Loh, Xian Jun; Wu, Yun-Long; Li, Zibiao
Abstract : Biodegradable polyester unimolecular systems are the future emerging materials for therapeutic applications. Abstract : Unimolecular micelles, as a class of single-molecular micelles, are structurally stable regardless of their concentrations or alterations of the outer environment such as pH, temperature, ion strength etc. in comparison with conventional polymeric micelles. Polyester unimolecular micelles are extensively applied in bio-medical fields because of their stability, biocompatibility, biodegradability, structural-controllabilty etc. In this review, the most recent developments in polyester unimolecular micelle designs in terms of Boltorn polymer H40 core, cyclodextrin, dendrimer or dendrimer-like polymer, or polyhedral oligomeric silsesquioxane (POSS) based polyester unimolecular micelles are presented. The significance and application in biomedical fields including drug delivery, bio-imaging and theranostics are also classified in this review. Finally, the remaining challenges and future perspectives for further development of unimolecular micelles as therapeutic materials are also discussed.